Islamic Law Analysis of MUI Fatwa No. 13 of 2021 Concerning the Law of Covid-19 Vaccination During Fasting - Elvia, Evi Eka (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The object of this study is the fatwa of the Indonesian Ulama Council (MUI) regarding the law of vaccination during fasting. This fatwa was made on the basis of an urgent interest regarding the law of whether or not to vaccinate while fasting. This study uses the nas and ushul fiqh approaches. The data used is to use 'illat (reason) reasoning. The theory used uses the istihsan theory. The interests on which it is based are the interests of the maslahah (public interest), taking into account five interests, namely maintaining religion, nurturing the soul, maintaining reason, maintaining offspring, and maintaining property. This research study contains three findings. First, MUI fatwas have been comprehensively compiled from various valid sources, the Qur'an, hadith, fiqh rules, and scholarly opinions so that there is no doubt about the legal provisions. Second, this fatwa connects and integrates science and religious knowledge that contributes to solving problems in the midst of the COVID-19 pandemic. Third, fatwa’s appear at the right time in the condition of people who urgently need legal clarity on the law of vaccination while fasting.